IRAQI Academic Admission System: A Performance Analysis Evaluation - Sami Hasan,; Al-Hamadani, Ammar A. Noori; Talib M. Jawad Al Taleb, (Iraqi Journal of Science, 2021)
The service quality of any information-based system could be evaluated by the high-end user in such a way that the system developer or responsible intently might use these user experiences to improve, develop and benchmark their system. In this paper, questionnaire implemented to rate to what extent the academic admission system as a web site achieves performance. Data were collected from 21 users of the system; all of them are highly educated and have the experience of using the site. Quadrant and gap analysis were implemented to evaluate the weakness and strength of the data. The major data analyses were performed on the data collected in terms of its importance and satisfaction to the users. A number of statistical tools have been utilized such as average value and standard deviation to accomplish the objective of this paper.